A case study on the implementation of MFCA in SMEs: HNJC company / Zhu Weidong ...[et al.] - Zhu, Weidong; Nukumi, Ryoichi; Zhang, Chen; Cheng, Pinlong (2009)
With the enhanced awareness of environmental protection, the importance of MFCAv(Material Flow Cost Accounting) is gradually increased. This paper discusses the background, environment cost and benefit, and performance evaluation of MFCA in SMEs (Small and Medium Enterprises) for the case ofHNJC Company. Several changes for happened in HNJC after MFCA introduced the process and tools of environmental management accounting, cost and revenue accounting and perfomance evaluation based on MFCA. From the case study, we found that HNJC reduced the output of waste or poor products in various processes and made successful technology investment on the production chain to transform the production process after the implementation of MFCA.